Investigating the Influence of Perceived Behavioral Control and Personal Innovativeness on the Adoption of Online Fashion Shopping among Generation X: A TAM Approach”: - Rafki, Rafnelly; Ramadhani, Annisa Suci; Ali, Hapzi; Ratnasari, Sri Langgeng (Dinasti International Journal of Digital Business Management, 2024)
Online shopping has experienced rapid growth in the digital age, and understanding the factors influencing the adoption of online shopping by Generation X is becoming important for businesses such as e-commerce, marketers, and researchers. The purpose of the study was to understand the interaction between Perceived Behavioral Control and Personal Innovativeness in influencing the intention of online fashion shopping adoption in Generation X. This research is quantitative and qualitative, using the TAM approach. A sample of 50 Generation X men and women born between 1965 and the 1980s were users of online fashion shopping applications. Varibel X, there are 2 namely Perceived Behavioral Control and Personal Innovativeness. Variable Y, is the Intention to Use Online Fashion Shopping Apps. Data analysis uses simple correlation tests, and descriptive statistics such as mean, median, and standard deviation. Analyzed using SPSS statistical software. Data analysis includes validity and reliability tests. Instrument, descriptive analysis, and linear regression test to test the effect of the independent variable on the dependent variable. Personal Innovativeness positively influences the Intention to Use Online Fashion Shopping. It was found that Perceived Ease of Use had a significant influence on Intention to Use Online Fashion Shopping. Perceived Usefulness also positively affects the Intention to Use Online Fashion Shopping. Research shows that the factors of the TAM approach, namely Perceived Ease of Use, Perceived Usefulness, Perceived Behavioral Control, and Personal Innovativeness, have an important role in influencing Generation X's intention to adopt Online Fashion Shopping. The research can also provide valuable insights for e-commerce companies and fashion industry players in developing and improving online shopping applications that are more attractive and easy to use for Generation X.